Short Communication: The emergence and rise of indigenous thermophilic bacteria exploration from hot springs in Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lischer K, Putra ABRD, Guslianto BW, Avilla F, Sitorus SG, Nugraha Y, Sarmoko. 2020. Short Communication: The emergence and rise of indigenous thermophilic bacteria exploration from hot springs in Indonesia. Biodiversitas 21: 5474-5481. Indonesia is an archipelagic country located in the pacific ring of fire, and is estimated to cause numerous hot springs spread across the country. In addition, small living microbes have been explored in these locations since 1985. These microbes possess the ability to survive in areas with high temperature (more than 40oC-90oC), and are therefore termed thermophiles. Hence, massive explorations have been conducted on Java island and other unexplored areas at Sumatra to Papua in New Guinea islands. Moreover, a total of 71 hot springs characterized by the presence of thermophilic bacteria have been explored in Indonesia. These investigations ensue with various approaches, including through conventional and microbiological, 16S rRNA, as well as whole-genome sequencing methods. In addition to species exploration, the application of thermophiles has become a topic of interest from 1999, especially based on thermostable enzymes with the capacity to maintain activity at high-temperature conditions. These include amylase, protease, lipase, xylanase, esterase, and cellulase as the most common isolated form, which indicates the existence of significant extractable potentials. Hence, there is a need for further research in terms of both exploration and application purposes.
Keywords: Hot spring, Indonesia, thermophilic bacteria, thermostable enzyme